ANALISIS YURIDIS TERHADAP PENYIMPANAN SERTIFIKAT HAK ATAS TANAH OLEH NOTARIS PADA PROSES PENGIKATAN JUAL BELI (PJB) (ANALISIS PUTUSAN NOMOR 53/PID.B/2017/PN.BKT) - Azhar, Dila Andika (Kopertis Wilayah X, 2019)
The sales and purchase agreement is a preliminary agreement whose made by the parties in front of the notary before they do the deed of sales and purchase in front of the Land-deed officials. In case of breach of contract occurence toward sales and purchase agreement, the Notary frequently reported to the authorities on charges of keeping the land rights certificates in the process of sales and purchase agreement, Eventhough the parties have agreed to place their sign or keep such evidence to the Notary. This case is apparent in the verdict Number 53/Pid. B/2017/PN. Bkt on defendant Elfita Achtar, a notary public who was reportedly due to kept and not given four (4) Building Rights Certificates owned by PT. Rahman Tamin